Efforts to Improve the Quality of Memorizing The Quran Surah Al-Baqarah Verse 143 through the Application of the Method Al-Qosimi for Students of Class VIII of State Junior High 16 - Farain, Nurul; Ridwan, Muhammad; Rusli, Rusli (Universitas Pahlawan Tuanku Tambusai, 2025)
This research is motivated by efforts to improve the quality of memorization of the Qur'an, especially Surah Al-Baqarah verse 143 through the application of the Al-Qosimi method. This method emphasizes repetition techniques and understanding the meaning of verses as a strategy to support the memorization process. This study aims to determine how to apply the Al-Qosimi method in an effort to improve the quality of memorization of the Qur'an, surah Al-Baqarah verse 143 in class VIII SMP Negeri 16 Buton Tengah. The research method used is the Classroom Action Research (CAR) method, with data collection techniques through observation, research, and documentation. The results of the study show that the Al-Qosimi Method has shown its effectiveness in improving the ability to memorize the Qur'an, especially in Surah Al-Baqarah verse 143, by helping students who previously had difficulty memorizing more easily in terms of pronunciation accuracy and understanding of the meaning of the verse. This approach is practical and can be applied both independently and with assistance from teachers.